THE TEACHERS' CLINIC. - Carson, A. B.; Anderson, Wilton T.; perry, Kenneth W.; Moss, Kermit C.; Mead, Stuart B. (The Accounting Review, 1957)
Abstract Students of accounting commonly have trouble with the so-called "goodwill method" of recording the admission of a new partner into a firm. Under this method, wherein the recorded capital equity of the old partners is not to be reduced and the credit to the new partner can be no less than his investment, there are the two problems of calculating the amount of goodwill to be recorded, and determining which partner or partners' capital accounts are to be credited when the goodwill is recorded. The determination of the amount of goodwill involved is approached by first calculating two amounts, both called recorded capital. The amount of goodwill involved is determined by subtracting what is termed invested capital from the larger of the two amounts of calculated recorded capital. Invested capital is the sum of the existing partners' capital equities before any adjustment for goodwill plus the contribution of the new partner. In presenting the material, the instructor must keep in mind that the students are not accounting majors. Further, he must remember that the students have enrolled in order to gain some practical knowledge. Due to the subject matter the course is difficult. Its usefulness, however, makes it a very popular elective.